Innovation and Digitalization as a Starting Point for Entrepreneurship Among Rawamangun Youth - Syafrudin, Iqbal; Sumadi, Tjipto; Maiwan, Mochamad (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
The background to this service is to increase the knowledge and understanding of political students at Universiti Sains Malaysia so that they can have knowledge and understanding of the important role of technology such as poster media in political education. As is known, many societal perspectives consider the existence and meaning of politics to be a positive thing, and there are also those who consider politics to be a negative thing. In fact, political Sains is very important to study because whether consciously or not, politics actually influences most human lives in society and the state. Through politics, people's lives depend on the decisions taken within them.